Mediterranean, DASH, and MIND Dietary Patterns and Cognitive Function: The 2-Year Longitudinal Changes in an Older Spanish Cohort - Nishi, Stephanie K.; Babio, Nancy; Gómez-Martínez, Carlos; Martínez-González, Miguel Ángel; Ros, Emilio; Corella, Dolores; Castañer, Olga; Martínez, J. Alfredo; Alonso-Gómez, Ángel M.; Wärnberg, Julia; Vioque, Jesús; Romaguera, Dora; et al. (Frontiers in Aging Neuroscience, 2021)
Background & Aims: Plant-forward dietary patterns have been associated with cardiometabolic health benefits, which in turn have been related to cognitive performance with inconsistent findings. The objective of the present study was to examine the relationship between baseline adherence to three a priori dietary patterns (Mediterranean, DASH, and MIND diets) with 2-year change in cognitive performance in older adults with overweight or obesity and high cardiovascular disease risk. Methods: A prospective cohort analysis was conducted within the PREDIMED-Plus trial, involving 6647 men and women aged 55-75 years with overweight/obesity and metabolic syndrome. Validated, 143-item semi-quantitative food frequency questionnaires completed at baseline were used to calculate dietary pattern adherence scores. An extensive neuropsychological test battery was administered at baseline and 2-year follow-up. Multivariable-adjusted linear regression models were used to assess associations between 2-year changes in cognitive function z-scores across tertiles of baseline adherence to the a priori dietary patterns. Results: Adherence to the Mediterranean diet at baseline was associated with 2-year changes in the general cognitive screening Mini-Mental State Examination (MMSE, β:0.070; 95% CI: 0.014, 0.175, P-trend = 0.011), and two executive function related assessments: the Trail Making Tests part A (TMT-A, β: -0.054; 95% CI: -0.110, -0.002, P-trend = 0.047) and part B (TMT-B, β: -0.079; 95% CI: -0.134, -0.024, P-trend = 0.004). Adherence to the MIND diet was associated with the backward recall Digit Span Test assessment of working memory (DST-B, β: 0.058; 95% CI: 0.002, 0.114, P-trend = 0.045). While higher adherence to the DASH dietary pattern was not associated with better cognitive function over a 2-year period. Conclusions: In older Spanish individuals with overweight or obesity and at high cardiovascular disease risk, higher baseline adherence to the Mediterranean dietary pattern may be associated with better cognitive performance, compared to lower adherence over a 2-year period.